RVA-Readiness: A Conceptual Framework for National Recognition, Validation, and Accreditation Systems (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2025)
This paper presents a comprehensive framework for understanding and implementing Recognition, Validation and Accreditation (RVA) systems at the national level, with particular attention to facilitating migrants and refugees. The concept of "RVA-readiness" is introduced as a multi-dimensional framework encompassing legal, institutional, professional, and societal prerequisites for effective RVA implementation. The essay argues that RVA-readiness requires a systematic approach that moves beyond technical procedures to embrace a holistic paradigm shift toward recognizing all forms of learning as valuable contributors to individual and societal development.This concept draws on comparative case study data collected during a UNESCO Institute for Lifelong Learning research initiative on the recognition, validation, and accreditation of prior learning for migrants and refugees in Latin America and the Caribbean, among other regions, being part of the Institute’s programme on “Recognition, Validation and Accreditation (RVA) for migrants and refugees”. Keywords: recognition of prior learning (RPL), recognition, validation and accreditation (RVA), lifelong learning, migration, national qualification frameworks, educational policy